CHALLENGES OF TEACHING PRACTICE IN THE POST-TRUTH ERA: REFLECTIONS ON FAKE NEWS AND EDUCATION - Barriento, André Luiz; Ribeiro, Marcel Thiago Damasceno (Seven Editora, 2024)
This study discusses the challenges faced by education in the Post-Truth Era and fake news, where the dissemination of false information and the relativization of truth directly impact teaching practice. The concept of Post-Truth, characterized by the prevalence of personal beliefs over objective facts, challenges the traditional role of the teacher as a mediator of knowledge. Based on Edgar Morin’s complexity theory and Clandinin and Connelly’s Narrative Research, this study argues that the adoption of a reflective posture is essential for teachers to face the challenges imposed by misinformation. Methodologies such as Discursive Textual Analysis and Narrative Research are proposed as effective tools in the sense of developing a critical education. The text also discusses the need to reformulate teacher training and to integrate public policies that promote critical thinking and digital literacy, preparing teachers to deal with the new informational dynamics of contemporary society. DOI:https://doi.org/10.56238/sevened2024.027-007